A Kinetic and Synthetic Approach of Surfactants Accelerated by Vilsmeier- Haack Acetylation and Formylation with Anisole - Iqubal, Dr. S. M. Shakeel (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Vilsmeier-Haack (VH) reactions are mostly too slow even at higher temperatures. However, quick and easy transformation was observed in micellar media even at moderate temperatures. Materials and Methods: Different types of surfactants (anionic – sodium dodecyl sulfate, cationic – cetyltrimethyl ammonium bromide, and non-ionic – T X-100) are used as micelle forming compounds. Results and Discussion: Micellar-mediated reactions exhibited dramatic rate accelerations and improvements in the yield of end products. The VH reactions pursued pseudo-first- and second-order kinetics. Conclusion: This study with anisole is the first such report demonstrating a feasible, controllable, non-toxic, and easy methodology for the synthesis of formylated and acetylated derivatives and a study of their kinetic behavior.